Rancang Bangun Sistem Monitoring Volume Air pada Tandon dengan Metode Kapasitif Berbasis IoT - Wijaya, Tanto; Ilyas Hadikusuma, Mohd; Chryostomos Hendro Yuwono, Yohanes; Ridhwan Sufandi, Muhammad; Rusyda Saufa, Nanda (entries, 2024)
This research focuses on developing an IoT-based capacitive sensing system for monitoring water volume in tanks, suitable for specific residential and industrial applications. The main capacitive sensor utilizes a 32 cm x 6 cm x 2 mm aluminum plate coated with resin to protect against moisture and contaminants. Initial evaluations demonstrated high sensitivity and rapid response in detecting liquid levels, with an 8.23% margin of error. However, further evaluation is necessary to address specific aspects such as resolution and response stability. Next steps include refining the design, conducting additional experiments, and optimizing sensor parameters. These findings aim to provide deeper insights into capacitive sensor technology and open new possibilities for its application across various technological contexts.